2017
DOI: 10.1002/ceat.201700226
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Control of Microbubble Properties by Alcohol Shear Flows in Ceramic Membrane Channels

Abstract: Efficient control of microbubbles is achieved by alcohol shear flows in ceramic membrane channels. The dependence of hydrodynamic and mass transfer properties of microbubbles on liquid viscosity was investigated in a bubble column. The multichannel ceramic membrane worked as the gas sparger, and the shear flow on the membrane surface controlled the microbubble generation. Oxygen gas and glycerin solutions with different viscosities served as gas phase and liquid phase, respectively. The microbubbles were massi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…5(a), it is clear that the majority of the bubbles generated by the CMM were spherical owing to the surface tension. 26,62 As the cross liquid velocity increased, shear stress increased; thus the bubbles became smaller and more uniform. As indicated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5(a), it is clear that the majority of the bubbles generated by the CMM were spherical owing to the surface tension. 26,62 As the cross liquid velocity increased, shear stress increased; thus the bubbles became smaller and more uniform. As indicated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, by adding internals [18][19][20][21] or changing operation conditions, [22][23][24] the bubble diameter can be effectively decreased, and thus the interfacial area increased. Alcohols, 25,26 surfactants 8,[27][28][29] and electrolytes [30][31][32] are typically added in coalescence systems to inhibit bubble coalescence 33 and increase bubble rigidity, 34 by which bubbles become smaller and a larger interfacial area is obtained. When the bubble size decreases to several micrometers (i.e., microbubbles [35][36][37] ), they exhibit unique properties, 38 e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The size of the macrobubble generated from the pipeline is nearly 1 cm. The macrobubble shows a fast rising velocity with a continually deformed shape due to its strong sensitivity to the surrounding flow field . However, the microbubble, generated by the gas distributor, moves sluggishly and shows a stable morphology due to the conspicuous interfacial tension …”
Section: Results and Discussionmentioning
confidence: 99%
“…The macrobubble shows a fast rising velocity with a continually deformed shape due to its strong sensitivity to the surrounding flow field. 29 However, the microbubble, generated by the gas distributor, moves sluggishly and shows a stable morphology due to the conspicuous interfacial tension. 29 The dependences of the mean bubble size on the nitrogen flow rate and the pore size of the distributor (PSD) are shown in Figure 1a.…”
Section: Methodsmentioning
confidence: 99%
“…The average diameter of microbubbles was found to significantly decrease with the increase of liquid flow velocity and the decrease of liquid surface tension. 19−21 Liu et al 22 found that liquid viscosity had a dual effect on the size of microbubbles obtained by a multichannel ceramic membrane. With increasing liquid viscosity, the Sauter diameter of microbubbles decreased first (μ < 2 mPa•s) and then increased slowly (2.0 < μ < 20 mPa•s).…”
Section: Introductionmentioning
confidence: 99%